NURSING PRODUCTION ON POST-PARTUM DEPRESSION - Nadieli Daandels; Éder Luís Arboit; Isabel Cristina Pacheco van der Sand (Universidade Federal do Paraná, 2013)
This is a narrative review aiming to characterize studies undertaken by nurses on post-partum depression. The search for publications occurred in two international databases, using the descriptors depression, postpartum and nursing; the study sample was made up of 15 articles. One of the nurses' central interests is in the early detection of women with signs which are predictive of depression; this is emphasized as a professional who, through the frequent contact with puerperas, has greater facility in undertaking triage and offering counselling regarding depression. It is noted that the nurses become involved with the production of knowledge on this issue and that the majority of the studies have a quantitative approach. The knowledge produced is directed, in particular, to the early detection of the depression, which evidences preoccupations with questions of the recovery of the woman's health and promotion of the appropriate development of the child.